"Índice de avaliação ecográfica no estudo de nódulos sólidos mamários: uma nova proposta de classificação - Clecio Enio Murta de Lucena (2006)
The Index of sonographic evaluation (ISE) in the study of solid breast tumors proposes an imaging classification using Ultrasound and Doppler technology. Objectives: to determine the validity of the "Index of sonographic evaluation" in the study of the solid breast tumors; to determine the behaviour of the variables of composition of ISE in the diagnosis for image of solid breast tumors; to compare the ISE with and without Doppler in the study of solid breast tumors. Patients and Method: a linear-sectional study was performed using 528 patients with 555 solidbreast tumors. The imaging classification and the histologic diagnosis of these patients were compared, in the period between March, 1999, and August, 2004. The parameters of the Index of Sonographic Evaluation consisted of four sonographic variables (contours, internal texture, posterior echo, relationship of the anteroposterior / longitudinal diameters) and the tumor vascularity pattern observed with Doppler. For each variable a score that varies from one to three was assigned, witheach tumor receiving a final score between 5 and 15: low suspicion (5, 6 or 7), intermediate suspicion (8, 9 or 10) or of high suspicion (11 to 15). In the composition of the alternative ISE the variable Doppler was excluded, with a final score varying between 4 and 12. To transform this classification in a binary variable, age was used as a criterion where lesions of intermediate suspicion in women less than 35 yearsold, were defined as Low Risk. Lesions of intermediate suspicion in women 35 or older as well as those of high suspition, were defined as High Risk. All the tumors underwent open biopsy removal. Results: 160 cases of breast cancer and 395 benign tumors were studied. The Index of Sonographic Evaluation defined 228 tumors as High Risk and 327 as Low Risk. Two cases of breast cancer were previously classified as Low Risk with the Index of Sonographic Evaluation. The results obtained demonstrate sensitivity of 98.8%, specificity of 82.3%, positive predictive value of 69.3% and negative predictive value of 99.4%. Using the Index ofSonographic Evaluation without Doppler, 342 tumors were classified as Low Risk and 213 as High Risk. Three cases of breast cancer were previously classified as Low Risk. Sensitivity of 98.1% was obtained, and specificity of 85.8%, positive predictive value of 73.7% and negative predictive value of 99.1%. An analysis of logistic regression of the combined evaluation of the variables of composition of the Index ofSonographic Evaluation demonstrated that the internal texture did not provide statistical significance. Conclusions: the "Index of sonographic evaluation consists of a methodology with high validity measures in the sonographic study of solid breast tumors; Contours, posterior echoes, relationship of the antero-posterior / longitudinal diameters and tumor vascularity pattern were the variables of composition of ISE thatdemonstrated statistical relevance, standing out the magnitude of the importance of the variable contours in the sonographic study of solid breast tumors; the comparative analysis between ISE with and without Doppler demonstrated similar results in the sonographic study of solid breast tumors.